Mobilex: a generic framework for cross-platform mobile development based on web language - Niemiec, William; Borges, Rafael; Cota, Érika (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2022)
Several mobile development frameworks allow developers to program a single code to run on different types of devices and operating systems. However, the application code is dependent on the chosen framework, making it difficult to reuse it when there is a need to migrate to other frameworks. This paper proposes a generic framework for cross-platform mobile development, which uses web technologies (HTML, CSS, and JavaScript) as a basis for application development. The use of this technology to define the application and its automatic translation to a platform-specific language makes it easier to produce and maintain the application on multiple platforms. This paper discusses the proposed approach and shows, through case studies, that it allows flexibility in the choice of cross-platform development framework, not being necessary to change the code already developed in case of change in the development platform. Video presentation:  https://youtu.be/ZS152tXUqBQ